Teachers' Roles in Applying Problem Solving Activity to Teach Speaking - Branigan, Laura Adhi Pramadhika (Universitas Negeri Surabaya, 2022)
The goal of this research is to find out the teacher’s roles in applying problem solving activity to teach speaking. This research was carried out on 1 English teacher and 1 group of 36 students. The participants were the tenth graders of SMKN 1 Jombang. Observation was done to find out the teacher’s knowledge about her roles in applying problem solving activity to teach speaking. Interview also was done to the teacher to know the roles in applying problem solving activity to teach speaking. The participants also demonstrated from the questionnaire to elicit their opinion about the effectiveness of applying problem solving activity to teach speaking. The result showed the tenth graders have a positive response towards the applying problem solving activity to teach speaking.